New Directions in Depression Treatment: Hopes, Challenges, and the Future of Integrated Psychiatry - Zuzanna Czuba; Martin Dahl (Cakrawala: Jurnal Pendidikan, 2025)
This article presents new directions in the treatment of depression, with particular emphasis on the development of the integrated approach in psychiatry. It discusses contemporary innovations in both psychotherapy and pharmacotherapy, including digital therapy, ketamine-assisted treatment, and the psychotherapeutic use of psychedelics. The article highlights the growing importance of holistic and humanistic approaches—especially Gestalt therapy—and the potential to combine technological advancements with the relational depth of traditional psychotherapy. The aim of the study is to establish a conceptual framework for understanding the future of mental health interventions in the context of increasing social and emotional complexity.